2006
DOI: 10.1097/01.mcd.0000198925.94082.ea
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity and phenotypic anomalies in children with atrioventricular canal defect and tetralogy of Fallot

Abstract: Tetralogy of Fallot associated with the atrioventricular canal defect has been usually reported in association with Down syndrome. The aim of the present study was to describe the cardiac aspects and the genetic anomalies in children with this association of heart defects. We identified 64 patients with atrioventricular canal defect tetralogy of Fallot. All children underwent complete cardiovascular, clinical phenotypic and genetic evaluation. A genetic syndrome or extracardiac anomalies were found in 56 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 41 publications
(57 reference statements)
6
10
0
1
Order By: Relevance
“…In our study patients with Down syndrome did not present coarctation of the PA, MAPCAs or coronary artery abnormalities. Furthermore, our study confirmed that pronounced dextroposition of the aorta is very rare in patients with Down syndrome 56. Our finding of a single patient with Down syndrome and SAA is in line with previous data showing SAA in one out of 43 patients 56.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study patients with Down syndrome did not present coarctation of the PA, MAPCAs or coronary artery abnormalities. Furthermore, our study confirmed that pronounced dextroposition of the aorta is very rare in patients with Down syndrome 56. Our finding of a single patient with Down syndrome and SAA is in line with previous data showing SAA in one out of 43 patients 56.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our study confirmed that pronounced dextroposition of the aorta is very rare in patients with Down syndrome 56. Our finding of a single patient with Down syndrome and SAA is in line with previous data showing SAA in one out of 43 patients 56. Thus, ToF in Down syndrome seems to be associated with a relatively uniform cardiac phenotype.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Prenatal exposures to ethanol, retinoic acid or theophylline with adrenergic agonists have been reported in humans with DORV 61 62. Of note, similar teratogens have been associated with TOF6365 and may influence pathways unique to type I DORV.…”
Section: Resultsmentioning
confidence: 99%
“…Esta cardiopatia, de difícil abordagem cirúrgica, apresenta uma associação conhecida com o SD 16 e provavelmente uma embriogénese particular nesta síndrome, uma vez que as duas cardiopatias apresentam origens embriogénicas muito distintas. [16][17] Nove por cento dos doentes da nossa amostra (9/102) foram submetidos a cirurgia paliativa. Destes, quatro corresponderam a shunts sistémico-pulmonares no contexto de ToF e em cinco casos foi realizado banding da artéria pulmonar em doentes com DCSAV, por apresentarem ventrículos desproporcionados, muito baixo peso, outras patologias não cardíacas associadas, com aumento do risco cirúrgico, ou HAP grave.…”
Section: Discussão E Conclusãounclassified